Analisis Faktor-Faktor Yang Mempengaruhi Impor Daging Sapi Diindonesia Tahun 1996 s.d 2017 - Ramadhan; Wardana, Ali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aims to determine how import prices, exchange rates, and GDP per.capitaof the number of imports of beef in the country of Indonesia from 1996 to 2017. The data usedare time series data. The analytical method used is multiple regression analysis with estimation using E-views 9. The research showed that import prices are hostile and not significant to Indonesia's number of beef imports. The exchange rate has a positive effect and no significant effect on thenumber of meat implications in the land of Indonesia and GDP per. Capita positive andsignificant impact on the number of imports of beef in the country of.Indonesia, the year 1996to 2017.